Pembelajaran Berbasis Projek Terhadap Kemampuan Pemahaman Konsep Siswa pada Materi Bangun Ruang Tabung di SMP - Simamora, Rona Marisa; Tambunan, Hardi; Pangaribuan, Firman (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the effect of project-based learning on students' conceptual understanding abilities in the topic of cylindrical three-dimensional shapes in junior high school. The type of research used is quasi-experimental with a pretest-posttest control group design. The research subjects consisted of 64 students, divided into an experimental class and a control class, each comprising 32 students. The research instrument was a conceptual understanding ability test consisting of essay questions. The data were analysed using the Shapiro-Wilk normality test, Levene's Test for homogeneity, and the independent two-sample t-test. The results showed that the posttest data of both classes were normally distributed and had homogeneous variances. The t-test indicated a significant difference between the conceptual understanding abilities of students in the experimental and control classes (Sig. = 0.006 < 0.05), with the experimental class posttest mean being higher. This indicates that project-based learning is effective in enhancing students' conceptual understanding skills. Project-based learning provides contextual learning experiences, encourages active student engagement, and strengthens meaningful understanding of mathematical concepts.